O papel educativo das rádios comunitárias : a vez da comunidade - Franco, Maristela de Oliveira (2009)
Community radio stations have an important role in the communities in which they belong to. And aside from being an open channel expression for the local population, community radio stations allow periphery citizens, which are technological, cultural and socially excluded, to make use of Hertz vibration to express themselves. The thousands of community radio stations uprising all over the country provides the beginning of a historical process of breaking the media monopoly. In relation to informal education, community radio stations help in the process of citizenship conquest through reflection and the awareness of the problems and of the public concern.